Antibacterial effect of silver nanoparticles on antibiotic resistant E. coli O157:H7 isolated from some dairy products - W. M. Elsherif; D. N. Ali (Bulgarian Journal of Veterinary Medicine, 2020)
Food safety is a worldwide health goal so foodborne diseases are a main health concern. A total 150 of dairy products samples (locally made yoghurt, ice cream and Talaga cheese) (50 for each type) were examined for E.coli O157:H7 detection and PCR confirmation using fliCH7 gene. E. coli O157:H7 was detected at 18%, 4%, 8% respectively, in samples. The isolates showed broad antibiotic resistance against vancomycin (84.6%), penicillin G (76.9%), cloxacillin (69.2%) and tetracycline (61.5%). Because of increasing number of microorganisms that are resistant to multiple antibiotics causing continuing economic losses in dairy manufacturing, there is an urgent need for development of alternative, cost-effective, and efficient antimicrobial agents to overcome antimicrobial resistance. Here, silver nanoparticle (AgNPs) solution was prepared, identified by transmission electron micros-copy (TEM) with an average size 26.5 nm and examined for bactericidal activity against E. coli O157:H7 by using well diffusion assay. The mean inhibition zones of 25 and 50 µg/mL concentrations of Ag-NPs were 15.0±1.2 and 20.9±1.4 mm, respectively. In addition, the statistical analysis showed highly significant differences in the bactericidal effect of different Ag-NPs concentrations on E. coli O157:H7 strains. Bacterial sensitivity to nanoparticles is a key factor in manufacture, so nanoparticles were considered suitable for long life application in food packaging and food safety.